The Secret Language of Competitive Intelligence: How to See Through and Stay Ahead of Business Disruptions, Distortions, Rumors, and Smoke Screens - Fuld, Leonard (Journal of Sustainable Competitive Intelligence, 2012)
THE ART OF SMART . . . how not to get blindsided by the competition Your key competitor has a cost advantage and you can’t for the life of you figure out why or how. • A new technology or competitor is on the horizon that will completely upset the applecart in your business as Google is now doing in advertising and Wal-Mart has done in retailing. • You think a key competitor may drastically drop prices or perhaps roll out a significant new product. What can you do to ascertain what their major moves will be? Competitive intelligence, the ability to see through or stay ahead of your competition, is the unspoken, hidden key to success. It is the means to knowing a customer’s strategic thinking, a rival’s cost structure when making a bid, or a competitor’s new product plans. Much as in a game of chess, you must think many moves ahead of your rivals—exactly the advantage competitive intelligence can give you. Leonard Fuld provides the tools to cut through the smoke screens and rumors that distort reality and shows: • How to avoid becoming your own worst enemy by removing blinders that can hide a competitor’s threatening moves • How to see your competitor’s vulnerability and take advantage of the easily exploitable opportunities it presents • How to run a war game to anticipate a rival’s pricing moves, new product introduction, or distribution strategy, and even to avoid being surprised by new entrants who play by different rules altogether For more than twenty-five years, Leonard Fuld has been developing groundbreaking ways for managers to stay two steps ahead of the competition, providing effective ways of finding out about pricing, new product rollouts, strategic alliances, outsourcing, and cost of operations. In The Secret Language of Competitive Intelligence he shows how to take data that is widely avail-able to everyone, think critically about it, and convert it into highly refined intelligence that leads to effective market-based decisions. Book Description Publication Date: May 23, 2006 Clique Aqui